Twelve tips for using Pattern Matching in data analysis for qualitative medical education research. (2nd November 2022) - Attard Cortis, Petramay; Muir, Fiona
Abstract: Pattern Matching (PM) is a data analysis method used in qualitative research. This article outlines a step-by-step approach to using PM to analyse qualitative data through the example of the author's experience in its use for a master in medical education dissertation. The recommended twelve tips, outlined as steps to be used sequentially in the PM process are: (1) Assess if PM is a suitable technique for you and your research, (2) Consider alternatives, (3) Decide to proceed with PM, (4) Perform literature review, (5) Reflect about your experiences, (6) Define Propositions, (7) Collect your data, (8) Code data, (9) Match data to propositions, (10) Celebrate congruency, (11) Explain discrepancies and, (12) Discuss relevance and utility of findings in your context. PM, when rigorously applied, can increase the internal validity and transferability of qualitative research in medical education. A clear data analysis protocol enhances reliability and dependability of any research.